Formulasi Sediaan Gummy Candies Sari Sawi Pakcoy (Brassica Rapa L) Dengan Variasi Sukrosa Sebagai Pemanis - Liza Zulaini; Gabena Indrayani Dalimunthe (CV. Pusdikra Mitra Jaya, 2025)
Pakcoy (Brassica rapa L.) is a type of green vegetable that is still a group with mustard. Pakcoy is a vegetable of immigrants from abroad. This vegetable is popular especially among people of Chinese descent. Sawi pakcoy contains vitamin A and vitamin C. The use of sawi pakcoy as a nutraceutical product is still relatively rare. The objective of this research was to find out that sawi pakcoy juice (Brassica rapa L.) can be made into preparations nutraceutical gummy candies and can find out which formula respondents prefer the most and the results of the best physical evaluation in gummy candies preparations. Samples of sawi pakcoy were formulated into gummy candies preparations with variations in sucrose concentrations of 115 mg, 230 mg, 345 mg, 460 mg, and 575 mg. All preparations were tested by organoleptic testing, weight uniformity, pH test, stability and hedonics by respondents of color, taste, aroma/smell, shape, and texture, then the results were compared to requirements in the literature. The results of the evaluation of gummy candies preparations state that gummy candies preparations meet physical quality. From the data it could be concluded that the preparation of gummy candies from sawi pakcoy’s essence showed the most preferred test results of gummy candies preparations, namely formula 5 with sucrose levels of 575 mg. The coefficient value of variation for the weight uniformity test was best compared to other formulas was formula 5 which was 575 mg. The pH value for the entire formula was 5. From stability tests it was known that the most stable formula was formula 5 which was stored at room temperature (25 °C).